(untitled) (Dhaka University Journal of Pharmaceutical Sciences, 2020)
The crude methanolic extract of the root bark of Pongamia pinnata was taken into consideration to isolate secondary metabolites. A total six known natural compounds were separated and purified by various chromatographic techniques and five isolates were identified as flavonoid derivatives such as pongachromene (1), kanugin (2), karanjin (3), demethoxykanugin (4), dimethoxypongapine (5) and the other is a triterpenoid (6). The pure compounds as well as petroleum ether, dichloromethane and ethyl acetate soluble fractions of crude methanolic extract were evaluated for bioactivities using established methods. In vitro antioxidant activity was studied by DPPH radical scavenging method using butylated hydroxyl anisole as standard. Among the pure compounds, kanugin and pongachromene showed significant antioxidant activity with the IC50 values of 27.20 ± 0.39 μg/mL and 43.53 ± 0.63 μg/ml, respectively as compared to the standard (23.87 ± 0.09 μg/ml), whereas karanjin, demethoxykanugin and dimethoxypongapine demonstrated moderate antioxidant activity. Mild thrombolytic activity was observed by different fractions with clot lysis ranging from 18.49 to 29.35% as compared to standard streptokinase (79.12%). The different solvent fractions and pure isolates showed very mild antimicrobial activity with zone of inhibition of 7.5 - 10.0 mm against the tested microorganisms using azithromycin and ketoconazole as standards. In the brine shrimp lethality bioassay, the dichloromethane, ethyl acetate, and methanol soluble fractions revealed significant lethality with LC50 values of 0.67 ± 0.05, 0.61 ± 0.13 and 0.56 ± 0.10 μg/ml, respectively as compared to standard tamoxifen (LC50 value 0.34 ± 0.09 μg/ml). Dhaka Univ. J. Pharm. Sci. 19(1): 1-8, 2020 (June)